Analysis of the incidence of intraocular metastasis. Issue 3 (March 1993) - Weiss, L
Abstract : The incidence of metastases to the uvea is compared with that in eight other (extraocular) target sites, in patients with metastatic primary carcinomas of the breast, colorectum, and lungs. The incidence of intraocular metastases from breast cancer is lower than in the eight other target organs surveyed; in the other primary cancers, the incidences were midway between those in the other sites, However, when the incidence of intraocular metastases is viewed in relation to the calculated numbers of cancer cells delivered via the arterial route, the uveal tract is the most highly favoured target site for the development of metastases per unit of delivered cancer cells.